Effect of weed control treatments and planting method on the yield and yield parameters of rice in Sudan savannah of Nigeria. - olanrewaju danmaigoro; Abdullahi Bilyaminu shittu; tukur abduljalil; Musa muhammad umar (International Journal of Applied Biology, 2022)
The experimentswerecarried out in 2020 and 2021 rainy seasons to determine the performance ofrice as influenced by planting method and weed control treatments. The treatments consists of three planting methods (dibbling broadcasting and transplanting and weed control methods (hoe weeding, pre emergence application of gramazone (200g/L of paraquat/ha), pre and post emergence of gramazone (200g/L of paraquat/ha) and propanil (360g/L of propanil + 200g/L 2-4D) and weedy check). The treatments were laid out in a randomized complete block design (RCBD) and were replicated three times.The results revealed the plots weeded twice and those treated with pre and post emergence application of gramazone and propanil respectively resulted in more number of spikelet per panicle, longer panicle, increase in number of effective tillers per hill, more grains per panicle and grain yield. The effect of planting methods on the rice growth revealed that rice sown under transplanting methods gave more number of effective tiler per hill, longer panicle, more grain per panicle and increases in grain yield compared to the others methods while broadcasting resulted in the least value of the parameters than others methods.Therefore,it can be concluded that rice farmers in the sudan savanna zone of Nigeria can adoptpre and post emergence application of gramazone and propanil with transplanting method since the combination of these treatments gave better weed control, growth and yield of paddy rice. Key words: Herbicide, length of panicle, number of grain per panicle andgrain yield